2013
DOI: 10.1080/01488376.2012.753977
|View full text |Cite
|
Sign up to set email alerts
|

‘Making It’ Versus Satisfaction: How Women Raising Young Children in Poverty Assess How Well They Are Doing

Abstract: Using in-depth interviews with 17 women raising young children in urban poverty, two separate standards were examined-"making it" and satisfaction. "Making it" referred to one's perceived ability to meet the basic physical needs of her children. In contrast, satisfaction referred to how closely one's current life circumstances align with her personal notions of success. Results indicated that self-expectations greatly influenced which standard individuals prioritized, such that those with higher expectations v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Often individuals perceive income adequacy in relation to those around them at home, work, or school. Wright's (2013) qualitative study of life satisfaction among a sample of women raising children in poverty concluded that "social comparisons played a figural role for participants in determining how satisfied they were with their lives. In contemplating their level of satisfaction, participants were much more likely to reference their relative poverty" (p. 274).…”
Section: Theoretical Underpinningsmentioning
confidence: 99%
“…Often individuals perceive income adequacy in relation to those around them at home, work, or school. Wright's (2013) qualitative study of life satisfaction among a sample of women raising children in poverty concluded that "social comparisons played a figural role for participants in determining how satisfied they were with their lives. In contemplating their level of satisfaction, participants were much more likely to reference their relative poverty" (p. 274).…”
Section: Theoretical Underpinningsmentioning
confidence: 99%
“…Raising children is one of the most rewarding and difficult things that parents are likely to do in life (Burrows and Keenan 2004;Dye 1992;Wright 2013). And what makes it even harder is that they do not come with instructions.…”
Section: Principles Of Training Up a Childmentioning
confidence: 99%
“…As a graduate student at Harvard Graduate School of Education, I studied Human Development and Psychology in order to better understand how risk and resilience interact in the lives of women and children developing in poverty. My dissertation work examined how women raising young children in poverty decide for themselves how well they are doing (Wright ). Since then, I have served as a school‐based mental health counselor; I have worked in early childhood education policy in Washington, DC; and I have, as a faculty member, prepared educators who will be responsive to the concerns and needs of homeless children.…”
Section: Positionalitymentioning
confidence: 99%